Analisis Strategi Promosi Dengan Memanfaatkan Media Sosial Dalam Meningkatkan Penjualan Produk Batik Di CV. Wery Group Kota Gunungsitoli - Lase, Kasiani; Mendrofa, Yupiter; Laia, Otanius; Harefa, Idarni (YUME : Journal of Management, 2025)
This study aims to analyze social media-based promotion strategies in increasing sales of batik products at CV. Wery Group Gunungsitoli City. A qualitative approach with descriptive method was used in this study, with data collected through interviews, observation, and documentation. The results showed that the use of social media, especially Facebook and Instagram, significantly affected the visibility of batik products. The promotional strategies applied, such as attractive visual content, active interaction with customers, and exclusive promotions, are proven to increase consumer interest. However, constraints were found in terms of consistency of content creation and lack of utilization of broader digital marketing features. Therefore, it is recommended that CV. Wery Group optimize its digital marketing strategy with a more structured and data-driven approach to increase promotional effectiveness. The conclusion of this study confirms that social media is an effective marketing tool if applied with the right strategy, as well as the need for regular evaluation and adjustment of the strategy to achieve optimal results.